The Effect of Jumping Exercises on Developing The Force Moments of Some Leg Muscles And Achievement of High Jump Activity For Youth (Journal of the College of Basic Education, 2025)
The progress in the sports level came as a result of the progress in the training process and the advancement of the level of methods and equipment and the preparation of trainers technically and practically, and keeping pace with different situations, and among the important training methods is the interest in training specific to biomechanical variables, and the aim of the research is to identify the values ​​of force moments for some of the working muscles of the legs, and to identify the effect of jumping exercises for the legs to develop force moments for some of the leg muscles and achieve the high jump activity for young people. The researcher used the experimental method by designing a single group with a pre- and post-test and applied the experiment to the experimental group, which consisted of (5) jumpers from young players from the Ministry of Sports and Youth - the Gifted School, and the pre- and post-tests were conducted, and the researcher concluded the necessity of building and preparing training programs to reach the required level in performance and achievement by developing force moments for some of the leg muscles because of their positive role in developing muscle strength and achieving the high jump activity.